Influence of adhesive and bonding material on the bond strength of bracket to bovine tooth - Bruna Lorena dos Santos Oliveira; Ana Rosa Costa; Américo Bortolazzo Correr; Marcus Vinicius Crepaldi; Lourenço Correr-Sobrinho; Julio Cesar Bento dos Santos (Universidade Estadual de Campinas, 2017)
Aim: To evaluate, in vitro, the effect of adhesive and bonding materials on the shear bond strength (SBS) of metallic brackets bonded to bovine teeth. Methods: Bovine teeth were embedded with acrylic resin, etched with 35% phosphoric acid for 20 s, rinsed, dried for 20 s and divided into 8 groups (n=20), according to the bonding materials and adhesive: Groups 1 and 5 - Transbond XT; Groups 2 and 6 - Fill Magic; Groups 3 and 7 - Biofix; and, Groups 4 and 8 - Orthocem. One layer of adhesive 3 M Unitek (Group 1), and one layer of Single Bond Universal Adhesive (Groups 2, 3 and 4) were applied and light-cured with LED for 10 s. Brackets were bonded to the buccal surface with four bonding materials and light-cured with LED for 40 s. SBS was carried out after 24 h and thermocycling (7,000 cycles - 5°/55 °C). Data were submitted to two way ANOVA and Tukey's post hoc test (α=0.05). The Adhesive Remaining Index (ARI) was evaluated at 8×. Results: The adhesive was effective in increasing the SBS for all bonding materials (p<0.05). Significant difference (p<0.05) on the SBS was observed between bonding materials with or without adhesive. The ARI showed a predominance of scores 0 for all groups. Conclusions: The adhesive improved significantly the SBS of the brackets to teeth. Different SBS values occurred among the bonding materials. ARI index showed predominance of score 0 for all groups.